Contract mining: an australian success story with a role to play in Latin America? - J. B. Greenwood (Instituto de Ingenieros de Minas del Peru, 1999)
The paper point out some reasons why contract mining should not achieve the same success in Latin America as it has in Australia. In this sense, any reasons are: the size of operation, mining industry employees bonus scheme, the privatization of nationalized mining assets, general sales tax and the mining unions. Therefore, great deal depends on the attitude or "mindset" of a company's employees. lt is strongly my view that the attitude with which a contractor approaches a job will give rise to a superior mindset amongst its employees when comparad to those from most mining companies. The value of this cultural difference is significant and should never be underestimated. lmportantly, it doesnot only manifest itself in a more productive workplace: it is invariably the case in Australia that the safety achievements of contract miners are superior to those generally expected from the mining industry at large.